Change of central hemodynamics of qualified athletes for testing the use of controlled breathing and evaluation - A.P. Romanchuk; V.V. Pisaruk (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Using spiroarteriocardiorhythmography surveyed 174 qualified athletes (121 male and 53 female). The examination consisted of three consecutive two-minute registrations - spontaneous, controlled breathing 6 and 15 breaths per minute. Found that the hemodynamic change substantially when the respiratory tests in the first place, cardiac output, cardiac index, total peripheral vascular resistance and specific peripheral vascular resistance. To develop criteria for evaluation of hemodynamic changes carried percentile variance analysis of all indicators in the performance tests. Testing of the evaluation criteria for different types of hemodynamics in athletes allowed to establish that eukinetic type characteristic is the reduction in heart rate and pulse blood pressure under test with controlled breathing 6 times per minute for hypokinetic - pronounced increase in systolic blood pressure and pulse blood pressure during the breath tests 6 and 15 times per minute for hyperkinetic - reducing end-diastolic volume, end-systolic volume, stroke volume, in vivo performance of both tests and an increase in systemic vascular resistance during test 15 breaths per minute.